The Role of Development Banks and Pan-Armenian Borrowings in Providing Economic Progress - Manaseryan, Tatul (Bulletin of Yerevan University G: Economics, 2018)
In the modern world, development banks (which are essentially different from ordinary banks) are called to play an important role in the development of the national economy. The Pan-Armenian Bank has been created as a Development Bank and is aimed at the purposeful and efficient use of Armenia’s and Armenian financial resources for the benefit of raising the competitiveness of Armenia's economy and improving the quality of life of the population.
Keywords: Development Bank, competitiveness, banking system, Diaspora